Value proposition as a framework for value co-creation in crowdfunding ecosystems. - Quero-Gervilla, María José; Ventura-Fernández, Rafael (SAGE, 2019)
The aim of this article is to explore whether the ecosystem approach is required to understand the new service model of crowdfunding. The value proposition approach offers different interpretations for each of the eight levels of value co-creation as seen in the service ecosystem. A qualitative multiple case-study approach is used to analyze the two most representative crowdfunding platforms in Spain, Verkami and La´nzanos, in terms of the amounts of funds provided. This article offers an analysis of specific cases of crowdfunding in the arts and cultural sector through the biggest platforms in Spain. The sampling design could be improved by including the experiences of crowdfunding projects in other countries in the analysis. The findings could assist service managers and practitioners to improve planning of value cocreation through the value propositions approach, with a variety of actors within the service ecosystem. This article is a contribution to the development of service-dominant (SD) logic in relation to FP 7 and FP 10. Managerial contributions include the development of a crowdfunding service ecosystem model for arts managers, which offers not only a method of generating finance or economic value but also opportunities for strengthening bonds with customers and other stakeholders. This article is unique in that it integrates value proposition categories in micro-, meso-, and macrocontexts and analyzes the different kinds of cocreation that exist in the crowdfunding context
Política de acceso abierto tomada de: https://beta.sherpa.ac.uk/id/publication/9379
Keywords: Crowdfunding; Empresas - Finanzas; Crowdfunding; Network; Service Ecosystem; Service Dominant Logic; Value Proposition; Value cocreation